Preparation of Indonesian sharia banks facing the 2023 global recession - FAKHRI HUSAINI - (Indonesia Auditing Research Journal, 2023)
The global recession in 2023 is predicted to occur before our eyes. If it does happen, the impact will extend to various sectors of life, one of which is the financial sector which is the heart of the economy. This research was conducted with the aim of seeing the readiness of Islamic banks in facing the 2023 recession. The method used in this research is descriptive qualitative method and library research. This method is used to explain and analyze the research object to suit the reality that is happening so that the writer can dig deeper and can review in detail how the experience of Islamic banks is in responding to the previous recession that has occurred in Indonesia. The data used in this study are secondary data in the form of journal articles, books, websites, and news that has relevance to this research. The results of the study explain that based on experience and statistical data, the Islamic banking sector is predicted to be resilient to shocks from the 2023 recession. One of the things that can hinder banking growth is the NPF, however, judging from the existing data, the NPF of Islamic banks tends to be low, so that it can be said that the financial condition Islamic banks are still healthy even though they were affected last year. by the pandemic. In facing the 2023 recession, the government has an important role to play in its policy to anticipate the impact of the recession, even though the Indonesian economy is still growing above 5% but one must be vigilant, especially against the storm of layoffs (PHK) that has recently hit a number of companies. The public is also advised to anticipate the impact of a recession